2000
DOI: 10.2135/cropsci2000.402555x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Yield Variation in Blue Grama and Little Bluestem Plant Collections in Southern Manitoba, Canada

Abstract: Inadequate seed supplies of adapted blue grama [Bouteloua gracilis (H.B.K.) Lag. ex Steud.] and little bluestem [Schizachyrium scoparium (Michx.) Nash.] cultivars limits the use of these two species in the northern Great Plains of Western Canada. This study examined variation in seed yield traits of 11 blue grama and 14 little bluestem plant collections obtained from southern Manitoba, Canada to facilitate development of improved germplasm of these species. Measurements of seed yield traits including harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Phan and Smith (2000) found differences among ecotypes for yield components of biomass including culms per plant (range was 176–302 culms plant −1 ) and seedheads per culm (range was 5.5 to 10.1 seedheads culm −1 ) in 3‐yr‐old spaced plants of little bluestem from 14 collection sites in Manitoba. They concluded that genetic diversity among indigenous collections was adequate for development of adapted cultivars with enhanced forage production.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Phan and Smith (2000) found differences among ecotypes for yield components of biomass including culms per plant (range was 176–302 culms plant −1 ) and seedheads per culm (range was 5.5 to 10.1 seedheads culm −1 ) in 3‐yr‐old spaced plants of little bluestem from 14 collection sites in Manitoba. They concluded that genetic diversity among indigenous collections was adequate for development of adapted cultivars with enhanced forage production.…”
Section: Resultsmentioning
confidence: 97%
“…Cornelius (1947) found spaced plants of all of the 26 ecotypes survived the winters at Manhattan, but severe winter injury occurred on Texas and Oklahoma ecotypes in seeded plots. Phan and Smith (2000) evaluated 14 ecotypes of little bluestem from Manitoba at Winnipeg and found biomass was highest for the southern ecotypes (138 g plant -1 ) and lowest for the northern ecotypes (50 g plant -1 ). Camper was chosen for this study because of its putative higher yield potential than northern strains and its high winter survival in seeded trials in the northern Great Plains (Jacobson et al, 1984).…”
Section: Within Camper Genetic Variation For Biomass Production and Mmentioning
confidence: 99%
“…These adaptive features have stimulated interest in cultivar development of this species (May et al, 1997; Smith and Phan, 1999). Since 1992, breeding efforts in blue grama have been made in Canada and shown the potential of generating an additional source of abundant, high‐quality seed specifically adapted to western Canada (Phan, 2000; Phan and Smith, 2000). However, challenges remain in improving seed production while simultaneously maintaining genetic diversity for adaptation in nonlocal environments (Smith and Whalley, 2002).…”
mentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Substantial research resources are often available for agronomic and horticultural crops and specifi c adaptation information is developed by extensive testing. Similar information is needed for native plants.…”
Section: Adaptation Regionsmentioning
confidence: 99%